Double-heterogeneous particle reinforced aluminum-based composite material and preparation method thereof

By introducing double heterostructure and nanoparticle reinforcement into the aluminum matrix, combined with cold rolling and heat treatment technology, the problem of strong plasticity contradiction of particle-reinforced aluminum matrix composite materials is solved, and the coordinated improvement of the strength and plasticity of the material is achieved.

CN119898086APending Publication Date: 2025-04-29YANSHAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510103022.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing particle-reinforced aluminum-based composite materials have a great contradiction in strong plasticity when applying loads, and it is difficult to simultaneously improve the strength and plasticity of the material.

Method used

Using a dual heterostructure design, the hard domain is formed by introducing fine crystal 6061 aluminum alloy and TiC nanoparticle reinforcement into the aluminum matrix, and alternately stacked with the coarse crystal 6061 aluminum alloy homogeneous material to form a soft domain. Combined with multi-pass cold rolling and heat treatment technology, a composite material with synergistic improvement in strength and plasticity is formed.

Benefits of technology

The strength and plasticity of the particle-reinforced aluminum-based composite material have been synergistically improved, the yield strength reaches 379.4MPa, the ultimate tensile strength reaches 405.7MPa, and the elongation reaches 12.7%, which significantly improves the comprehensive mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898086A_ABST
    Figure CN119898086A_ABST
Patent Text Reader

Abstract

The invention relates to a double-heterogeneous particle reinforced aluminum-based composite material and a preparation method thereof, and belongs to the technical field of composite materials, the composite material comprises nine layers of hard regions and soft regions which are alternately stacked, the hard regions are composite materials composed of fine-grain 6061 aluminum alloy and TiC nano-particle reinforcement bodies, and the soft regions are coarse-grain 6061 aluminum alloy homogeneous materials. The preparation method comprises the following steps: alternately stacking the hard regions and the soft regions, and sintering into the 9-layer double-heterogeneous particle reinforced aluminum matrix composite material by adopting a spark plasma sintering technology. The sintered composite material is subjected to multi-pass cold rolling, a cold-rolled plate is subjected to solution treatment for 30 min at the temperature of 570 DEG C and then subjected to aging treatment for 3 h at the temperature of 175 DEG C, the peak aging performance is achieved, the yield strength of the material is 379.4 MPa, the ultimate tensile strength is 405.7 MPa, and the ductility is 12.7%. According to the obtained particle reinforced aluminum matrix composite material, strength-plasticity synergistic improvement is achieved, and the excellent mechanical property is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and particularly relates to a double heterogeneous particle reinforced aluminum-based composite material and a preparation method thereof. Background Art

[0002] Particle-reinforced aluminum-based composites are often used as most aerospace structural components due to their excellent comprehensive properties such as high specific strength, light weight, high specific modulus, good thermal conductivity and corrosion resistance. When a load is applied to a particle-reinforced aluminum-based composite, the force is transferred from the softer aluminum matrix through the aluminum matrix-particle reinforcement interface to the hard particle reinforcement, which increases the strength of the material, but the particle reinforcement also causes a significant decrease in the plasticity and ductility of the material.

[0003] The concept of heterogeneous structure design is one of the important methods to achieve the synergistic improvement of strength and plasticity of metal materials, and it is increasingly favored by researchers of metal structural materials. The simultaneous introduction of soft and hard domains with huge differences in strength and hardness into the material makes it easier for dislocations to accumulate and interact during deformation, thereby producing higher heterogeneous deformation-induced strengthening and obtaining excellent strength-plasticity matching. At present, the introduction of heterogeneous structures into particle-reinforced materials has become an important solution to the contradiction between strength and plasticity, such as layered structures, core-shell structures, and double heterogeneous structures. Among them, double heterogeneous structures are considered to be a very promising strategy, in which the grains of the matrix present a bimodal distribution and the reinforcement particles present an inhomogeneous distribution. Soft and hard domains with large differences in strength and hardness are formed, and strain gradients are generated on the domain interfaces, forming geometrically required dislocations (GNDs), making the hard domain softer and the soft domain harder. Theoretical analysis shows that the reason for strong plastic coordination is the limitation of the domain interface. Dislocation pile-up is formed near the domain interface in the soft domain. As the dislocation pile-up continues to intensify, these dislocations form a force that acts on the dislocation source and suppresses its emission of dislocations. At this time, the dislocation source needs to increase the external stress to stimulate dislocations. The external stress is the heterogeneous deformation induced stress, which avoids the occurrence of premature necking and thus improves plasticity.

[0004] Nowadays, the preparation of particle-reinforced aluminum-based composite materials by spark plasma sintering technology has become a mainstream powder metallurgy method. It uses a strong DC pulse current to generate local discharge between metal powders, generate Joule heat to heat the sample, and can break through the oxide film on the surface of the metal powder to promote the formation of sintering necks, so that the prepared particle-reinforced aluminum-based composite materials are quickly dense. At the same time, due to the short sintering time and low sintering temperature, hard and brittle phases that deteriorate the performance will not be generated, and the grains will not grow excessively. Therefore, a new method for preparing double heterogeneous particle-reinforced aluminum-based composite materials can be formed based on spark plasma sintering technology. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a double heterogeneous particle reinforced aluminum-based composite material and a preparation method thereof. The double heterogeneous particle reinforced aluminum-based composite material provided by the present invention has the advantages of synergistically improved strength and plasticity.

[0006] To achieve the above object, the present invention discloses the following technical solution:

[0007] On the one hand, the present invention provides a double heterogeneous particle reinforced aluminum-based composite material, which includes nine layers of hard domains and soft domains that are alternately stacked and cold-rolled, the hard domain is a composite material composed of fine-grained 6061 aluminum alloy and TiC nanoparticle reinforcement, and the soft domain is a coarse-grained 6061 aluminum alloy homogeneous material.

[0008] Preferably, the volume ratio of 6061 aluminum alloy to TiC nanoparticle reinforcement in the hard domain is 99.5:0.5.

[0009] On the other hand, the present invention provides a method for preparing a double heterogeneous particle reinforced aluminum matrix composite material, which comprises the following steps:

[0010] S1, using the soft domain as the first layer and alternately stacking and compacting nine layers of hard domain and soft domain material powders to prepare a 9-layer composite material by spark plasma sintering;

[0011] S2, performing multiple cold rolling on the composite material with a reduction of 90%, and performing annealing at 400° C. for 10 min at a reduction of 50%;

[0012] S3. After multiple cold rollings, the rolled composite material is heat treated, the heat treatment includes solution heat treatment and aging heat treatment, the insulation temperature of the solution heat treatment is 550-570°C, the insulation time of the solution heat treatment is 5-60min, the insulation temperature of the aging heat treatment is 150-200°C, the insulation time of the aging heat treatment is 1-5h, and after the heat treatment is completed, a double heterogeneous particle reinforced aluminum-based composite material is obtained.

[0013] Preferably, in step S3, the solution heat treatment is carried out at a holding temperature of 570° C. and a holding time of 30 min.

[0014] In step S3, the aging heat treatment has a holding temperature of 175° C. and a holding time of 3 h.

[0015] Preferably, the composite material after cold rolling includes three deformation stages, the first deformation stage is an elastic deformation process, which is the same as that of a homogeneous material; the second deformation stage is an elastic-plastic transition process, in which stress activates the dislocation source in the soft domain to cause plastic deformation, while the hard domain still maintains elastic strain, resulting in mechanical incompatibility, and the hard domain constraint limits and increases the strain of the soft domain, and a strain gradient is generated at the domain interface, and the properties of the soft domain and the hard domain are changed by coordination of geometrically necessary dislocations to improve the overall yield strength, and dislocations accumulate at the soft domain interface, and the dislocation source needs to increase stress to stimulate dislocations, and heterogeneous deformation-induced stress is generated by the accumulation of geometrically necessary dislocations to strengthen the soft domain; the third deformation stage is a surface strain distribution process, in which continuous strain causes the hard domain to begin plastic deformation, strain distribution increases the strain of the soft domain, and the strain gradient at the boundary between the soft domain and the hard domain increases, and strain hardening ability is provided by the accumulation of more geometrically necessary dislocations to prevent necking, so that the composite material has both high strength and high plasticity.

[0016] Preferably, step S1 specifically includes the following sub-steps:

[0017] S11, preparing hard domain powder: putting 99.5 vol.% 6061 aluminum alloy powder and 0.5 vol.% TiC nanoparticle reinforcement into a planetary ball mill for ball milling and mixing, wherein the planetary ball mill includes three kinds of steel balls, the diameters of the three kinds of steel balls are 8 mm, 6 mm, and 2 mm, respectively, the mass ratio is 2:3:5, and the ball-to-material ratio is 8:1, to obtain the hard domain powder after ball milling;

[0018] S12. Alternately stack 9 layers of coarse-grained 6061 aluminum alloy powder and ball-milled hard domain powder, compact them, and place them in a spark plasma sintering system to apply temperature and pressure to prepare a sintered 9-layer composite material.

[0019] Preferably, the obtained dual heterogeneous particle reinforced aluminum-based composite material has a yield strength of 379.4 MPa, an ultimate tensile strength of 405.7 MPa, and an elongation of 12.7%.

[0020] Preferably, the particle size of the fine-grained 6061 aluminum alloy powder is less than 10 microns, the particle size of the TiC nanoparticle reinforcement is 50 nanometers, and the particle size of the coarse-grained 6061 aluminum alloy powder is greater than 45 microns and less than 150 microns.

[0021] Preferably, in step S11, argon is used as the protective atmosphere during the powder loading process; the planetary ball mill operates for a total time of 2-2.5 hours, and stops for 10 minutes after operating for 15 minutes, with a rotation speed of 150-250 rpm.

[0022] Preferably, in step S12, the sintering temperature and pressure increase process is: the temperature is increased to 20°C from 0min to 2min; the temperature is increased to 100°C from 2min to 6min; the temperature is increased to 200°C from 6min to 12min; the temperature is increased to 300°C from 12min to 20min; the temperature is increased to 400°C from 20min to 32min; the temperature is increased to 530°C from 32min to 48min; the temperature is increased to 540°C from 48min to 50min; the temperature is increased to 550°C from 50min to 52min; the temperature is increased to 560°C from 52min to 54min; the temperature is maintained at 560°C from 54min to 57min; and the pressure is maintained at 50MPa from 2min to 57min.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The double heterogeneous particle reinforced aluminum-based composite material obtained by the preparation method of the double heterogeneous particle reinforced aluminum-based composite material proposed in the present invention has excellent mechanical properties with synergistic improvement of strength and plasticity. The results of the embodiments of the present invention show that the yield strength of the double heterogeneous particle reinforced aluminum-based composite material provided by the present invention reaches 379.4MPa, the ultimate tensile strength reaches 405.7MPa, and the elongation reaches 12.7%. Its comprehensive mechanical properties are significantly improved compared with the prior art.

[0025] (2) The composite material proposed by the present invention is formed by alternating hard domains formed by fine-grained 6061 aluminum alloy and TiC nanoparticle composite materials and soft domains formed by coarse-grained 6061 aluminum alloy homogeneous materials. Multiple cold rolling passes were used, and the final reduction was 90%. Compared with the ordinary control group, the double heterogeneous particle reinforced aluminum-based composite material after cold rolling has a good strength-plasticity match, which is attributed to the mechanical incompatibility caused by the difference in strength and hardness of the soft and hard domains during strain, forming dislocation pile-up. The dislocation source requires heterogeneous deformation-induced stress to be stimulated to increase the strength. In the end, the hard domain becomes "soft" and the soft domain becomes "hard", and the accumulated geometrically required dislocations provide HDI hardening ability and improve plasticity. Subsequently, heat treatment under different conditions was carried out. After solution treatment at 570°C for 30 minutes, the precipitated phase was completely dissolved, and the double heterogeneous particle reinforced aluminum-based composite material was completely recrystallized, with the best comprehensive mechanical properties.

[0026] (3) In the preparation method of the double heterogeneous particle reinforced aluminum matrix composite material proposed in the present invention, different heat treatment conditions are combined with mechanical analysis to obtain the optimal solid solution-aging treatment conditions. The double heterogeneous particle reinforced aluminum matrix composite material after solid solution is subjected to aging treatment at 150-200℃ for 1-5h. Different aging treatment temperatures have peak aging performance. 175℃ is selected as the optimal aging temperature and 3h is the optimal aging time. At this time, a large amount of β" phase is distributed in the matrix, which is the peak aging state, which can ensure the high strength of the material. The obtained composite material has excellent mechanical properties with synergistic improvement of strength and plasticity. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the overall process of the present invention;

[0028] Figure 2 OM image of the sintered double heterogeneous particle reinforced aluminum matrix composite material prepared in Example 1 of the present invention;

[0029] Figure 3 OM image of the cold-rolled double heterogeneous particle reinforced aluminum matrix composite material prepared in Example 2 of the present invention;

[0030] Figure 4 OM image of the double heterogeneous particle reinforced aluminum matrix composite material prepared in Example 3 of the present invention after 570° C. solution heat treatment for 5 minutes;

[0031] Figure 5 OM image of the double heterogeneous particle reinforced aluminum matrix composite material prepared in Example 4 of the present invention after 570° C. solid solution heat treatment for 30 minutes;

[0032] Figure 6 This is the OM image of the double heterogeneous particle reinforced aluminum matrix composite material prepared in Example 5 of the present invention after 570° C. solution heat treatment for 60 min;

[0033] Figure 7 TEM image of the double heterogeneous particle reinforced aluminum matrix composite material prepared in Example 6 of the present invention after aging heat treatment at 175°C for 1h;

[0034] Figure 8 TEM image of the double heterogeneous particle reinforced aluminum matrix composite material prepared in Example 7 of the present invention after aging heat treatment at 175°C for 3 hours;

[0035] Fig. 9 This is a TEM image of the double heterogeneous particle reinforced aluminum matrix composite material prepared in Example 8 of the present invention after aging heat treatment at 175°C for 5 hours. DETAILED DESCRIPTION

[0036] The exemplary embodiments, features and aspects of the present invention will be described in detail below with reference to the accompanying drawings. The same reference numerals in the accompanying drawings represent elements with the same or similar functions. Although various aspects of the embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless otherwise specified.

[0037] On the one hand, the present invention provides a double heterogeneous particle reinforced aluminum-based composite material, which includes nine layers of hard domains and soft domains alternately stacked with each other, the hard domain is a composite material composed of fine-grained 6061 aluminum alloy and TiC nanoparticle reinforcement, and the soft domain is a coarse-grained 6061 aluminum alloy homogeneous material. The volume ratio of 6061 aluminum alloy to TiC nanoparticle reinforcement in the hard domain is 99.5:0.5.

[0038] The double heterogeneous particle reinforced aluminum-based composite material of the present invention forms a variety of strengthening mechanisms, such as Orowan strengthening, load-bearing strengthening and Talor strengthening, by introducing TiC nanoparticle reinforcement into the hard domain on the basis of fine grain strengthening provided by hard domain nanocrystals. The hardness difference between the soft and hard domains is further improved, and the hardness difference reaches 64.09%. The deformation process is divided into three deformation stages. In the first deformation stage, the soft domain and the hard domain participate in elastic deformation together, and the process is similar to that of homogeneous materials; in the second deformation stage, the stress first activates the dislocation source inside the soft domain, so that it emits dislocations and plastic deformation on the slip plane. At this time, the hard domain is still in an elastic strain state, and mechanical incompatibility is generated at the interface between the two. Due to the rigid constraint of the hard domain on the soft domain, the soft domain cannot deform freely. Since the soft domain deforms first, it will bear more strain during the deformation process, and the strain is continuous at the domain interface. Therefore, a strain gradient is generated near the domain interface, which requires geometrically necessary dislocations to coordinate. This will make the soft domain harder and the hard domain softer, thereby improving the yield strength of the material as a whole. Due to the limitation of the domain interface, dislocation pileups are formed near the domain interface in the soft domain. As the dislocation pileups continue to intensify, these dislocations form a force that acts on the dislocation source and inhibits its emission of dislocations. At this time, the dislocation source needs to increase the applied stress to continue to stimulate dislocations. The additional stress caused by the pileup of geometrically necessary dislocations is called back stress, which acts on the soft domain. At the same time, the force generated by the pileup of geometrically necessary dislocations also acts on the hard domain, which is called front stress. The combination of back stress and front stress is collectively referred to as heterogeneous deformation induced stress. Ultimately, this will make the coarse grains stronger, and the yield strength is even much higher than the prediction of the mixing rule. In the third deformation stage, with the continuous loading of strain, fine grains, i.e. hard domains, will also participate in plastic deformation. Due to the existence of strain distribution, the soft domain is subjected to higher strain than the hard domain. When adjacent domains are subjected to different plastic strains, there will be strain gradients near the boundaries of soft and hard domains. These strain gradients will increase with the increase of strain distribution, and more geometrically necessary dislocations are required to coordinate. These accumulated geometrically necessary dislocations provide additional strain hardening capacity, which helps to prevent necking during tensile testing, thereby improving plasticity. Therefore, the composite material provided by the present invention has excellent properties of high strength and high plasticity.

[0039] In the tensile fracture morphology, it was observed that the larger cracks in the hard domain stopped growing and became blunted at the interface with the soft domain. This indicates that the soft domain effectively prevented the crack from further expanding, a phenomenon that has also been observed in other heterogeneous structures. The underlying mechanism is that the soft domain provides more space for dislocation movement, facilitating dislocation migration, thereby contributing to crack blunting.

[0040] The improvement in hardness is mainly attributed to grain refinement and the presence of TiC particles. The addition of TiC nanoparticle reinforcement significantly improves the strength of the material. When particle-reinforced aluminum matrix composites are subjected to stress, multiple strengthening mechanisms work together. TiC nanoparticles with a diameter of less than 1 μm promote the Orowan strengthening mechanism, which can be expressed by the following formula:

[0041]

[0042] Among them, G M is the shear modulus of the aluminum matrix, b is the Burgers vector of the aluminum matrix, V p is the volume fraction of reinforcing particles, d p is the size of the reinforcing particles and Φ is the proportionality constant.

[0043] When external forces are applied to DPRAMCs, dislocations cannot pass through the TiC nanoparticle reinforcements. Instead, the TiC nanoparticles pin the dislocations, causing them to bend and form Orowan dislocation loops. When there is a significant hardness difference between the aluminum alloy matrix and the TiC nanoparticles, stress is transferred from the aluminum alloy matrix through the aluminum alloy matrix-TiC interface to the TiC nanoparticles. These nanoparticles then bear a larger proportion of the stress, thereby increasing the strength. This load-bearing strengthening effect is represented by the following formula:

[0044] Δσ=0.5V p σ Al

[0045] Among them, σ Al is the yield strength of the aluminum alloy matrix, V p is the volume fraction of reinforcing particles.

[0046] During the preparation process of DPRAMCs, including sintering and subsequent solution treatment, dislocations are formed at the interface between the reinforcement and the matrix when cooling to room temperature due to the significant difference in thermal expansion coefficients between the aluminum alloy matrix and the TiC nanoparticles. This leads to Taylor strengthening, as shown in the following formula:

[0047] Δσ=βGbρ 1 / 2

[0048] Where β is a constant, G is the shear modulus of the aluminum matrix, b is the Burgers vector of the aluminum matrix, and ρ is the dislocation density.

[0049] Therefore, Orowan strengthening, load-bearing strengthening, Taylor strengthening, and grain refinement strengthening lead to a significant strength difference between the hard and soft domains, which in turn produces the HDI effect and achieves a synergistic enhancement of the strength and ductility of cold-rolled DPRAMCs. After solution heat treatment, the increase in elongation (EL) and the decrease in yield strength / tensile strength (YS / UTS) are mainly attributed to recovery and recrystallization. However, when the solution time is increased from 5 to 30 minutes, an increase in both YS and UTS is observed, which is due to the dissolution of Mg2Si and AlFe(MnCr)Si phases. The high diffusion rate of Mg and Si atoms in the aluminum alloy matrix leads to rapid dissolution of solute atoms. Therefore, with the increase of solution time, the concentration of solute atoms increases, aggravating the lattice distortion and increasing the resistance to dislocation movement. When the solution treatment time is extended to 60 minutes, the strength decreases. This is caused by significant grain growth, which can be described by the Hall-Page relationship as shown in the following formula:

[0050] σ y =σ 0y +k y ·μ d -1 / 2

[0051] Among them, σ 0y is the internal friction of dislocation motion within the grain, k y is the Hall-Page slope, σ y is the yield strength at room temperature, μ d is the average grain size.

[0052] Coarse grains lead to a decrease in grain boundary density, which is a key factor in hindering dislocation movement, thus reducing strength. Prolonging the solution treatment time will lead to abnormal grain growth in the hard domain, reducing strength while increasing ductility. After heat treatment of aluminum alloys, a common phenomenon is that high strength is accompanied by low ductility. This behavior is partly due to the reduction in strain hardening ability, which impairs the material's ability to accumulate and store dislocations within the grains, making it more susceptible to local plastic instability. On the other hand, the grain boundaries in the second phase soft domain act as strong pinning sites, limiting dislocation movement. This reduces the number of dislocations crossing the soft domain boundaries, reduces the number of GNDs, weakens HDI hardening, and ultimately fails to improve ductility. In the present invention, a synergistic enhancement of strength and ductility is observed, which is attributed to the hardening of the soft domain by HDI stress, thereby increasing strength. The geometric strain gradient between the soft and hard domains further promotes HDI hardening, preventing necking and improving ductility in tensile tests.

[0053] In another aspect, the present invention provides a method for preparing a double heterogeneous particle reinforced aluminum matrix composite material, such as Figure 1 As shown, it includes the following steps:

[0054] S1. Use the soft domain as the first layer and the last layer and alternately stack nine layers of soft domain and hard domain material powders, i.e., a total of 5 layers of soft domain powder and 4 layers of hard domain powder, the odd-numbered layers are soft domain powder, and the even-numbered layers are hard domain powder, and prepare 9 layers of composite materials by spark plasma sintering.

[0055] S2. The composite material is subjected to multiple cold rolling with a reduction of 90%, and an annealing treatment at 400° C. for 10 min is performed when the reduction is 50%.

[0056] S3. After multiple cold rollings, the rolled composite material is heat treated, and the heat treatment includes solution heat treatment and aging heat treatment. The insulation temperature of the solution heat treatment is 550-570°C, the insulation time of the solution heat treatment is 5-60min, the insulation temperature of the aging heat treatment is 150-200°C, and the insulation time of the aging heat treatment is 1-5h. After the heat treatment is completed, a double heterogeneous particle reinforced aluminum-based composite material is obtained.

[0057] At the same time, after comparison and analysis, in step S3, the solution heat treatment, the insulation temperature of the solution heat treatment is 570°C, the insulation time is 30 minutes; in step S3, the insulation temperature of the aging heat treatment is 175°C, the insulation time is 3 hours. Through the solution heat treatment and aging heat treatment in this range, the mechanical properties of the composite material are optimal.

[0058] The embodiment of the present invention is composed according to the above-mentioned technical scheme, and fine-grained 6061 aluminum alloy powder + TiC nanoparticle reinforcement and coarse-grained 6061 aluminum alloy powder are stacked and sintered in 9 layers to obtain an alloy ingot; in this embodiment, the fine-grained 6061 aluminum alloy powder is preferably a powder with a particle size of less than 10μm, the TiC nanoparticle reinforcement is preferably a powder with a particle size of 50nm, and the coarse-grained 6061 aluminum alloy powder is preferably a powder with a particle size of 45-150μm.

[0059] In this embodiment, 99.5 vol.% fine-grained 6061 aluminum alloy powder and 0.5 vol.% TiC nanoparticle reinforcement are preferably pre-treated and prepared; the preparation is preferably carried out in a glove box and argon is used as a protective gas during loading; in the present invention, the ball mill is preferably a tungsten steel ball mill; the diameter ratio of the three steel balls is preferably 8 mm, 6 mm, and 2 mm, and the weight ratio is preferably 2:3:5; the ball-to-material ratio is 8:1. In the present invention, the ball milling in step S1 includes the following steps:

[0060] The fine-grained 6061 aluminum alloy powder and the TiC nanoparticle reinforcement are mixed in a planetary ball mill, and the rotation speed of the planetary ball mill is 150-250 rpm, and more preferably 200 rpm. In a specific embodiment of the present invention, the planetary ball mill is most preferably operated for 2-2.5 hours, preferably 2 hours, and is stopped for 10 minutes after every 15 minutes of operation.

[0061] In a specific embodiment of the present invention, the sintering in step S1 includes the following steps:

[0062] The 9-layer composite material was sintered in a spark plasma system. The temperature and pressure during sintering were as follows: 0min-2min, the temperature was raised to 20°C; 2min-6min, the temperature was raised to 100°C; 6min-12min, the temperature was raised to 200°C; 12min-20min, the temperature was raised to 300°C; 20min-32min, the temperature was raised to 400°C; 32min-48min, the temperature was raised to 530°C; 48min-50min, the temperature was raised to 540°C; 50min-52min, the temperature was raised to 550°C; 52min-54min, the temperature was raised to 560°C; 54min-57min, the temperature was kept at 560°C. The pressure was kept at 50MPa from 2min to 57min. The cooling method of sintering was cooling with the furnace and unloading the pressure to obtain the composite material.

[0063] In a specific embodiment of the present invention, the multi-pass cold rolling in step S2 includes the following steps:

[0064] The composite material is subjected to multi-pass cold rolling, and the number of multi-pass cold rolling is preferably 7-12 times, and more preferably 9 times; in a specific embodiment of the present invention, when the rolling deformation is 50%, annealing is performed at 400°C for 10 minutes. The multi-pass rolling is preferably performed in a two-roll flat rolling mill, and the pressing amount of each rolling is preferably 1.5-2mm. The total deformation of the alloy ingot after the multi-pass cold rolling is preferably 90%.

[0065] In a specific embodiment of the present invention, the heat treatment in step S3 includes the following steps: solution heat treatment and aging heat treatment; first, the composite material after multiple cold rolling is subjected to solution heat treatment, the holding temperature of the solution heat treatment is preferably 570°C, and the holding time of the solution heat treatment is preferably 5-60min, more preferably 30min; then, the composite material after the solution heat treatment is subjected to aging heat treatment, the holding temperature of the aging heat treatment is preferably 150-200°C, more preferably 175°C, and the holding time of the aging heat treatment is preferably 1-5h, more preferably 3h.

[0066] The present invention can completely dissolve the precipitated phase after solution heat treatment, causing lattice distortion, improving strength, and promoting the recrystallization process; the present invention can precipitate the second phase after aging heat treatment, and improve strength through precipitation strengthening.

[0067] After the heat treatment, the obtained alloy plate is post-treated to obtain a high-strength and high-plasticity dual heterogeneous particle reinforced aluminum-based composite material; in the present invention, the cooling method for the solid solution heat treatment is water cooling, and the cooling method for the aging heat treatment is air cooling.

[0068] The present invention provides the application of the high-strength and high-plasticity double heterogeneous particle reinforced aluminum-based composite material of the above technical solution or the high-strength and high-plasticity double heterogeneous particle reinforced aluminum-based composite material prepared by the preparation method of the above technical solution in the fields of fighter jets such as ventral fins or automobile parts such as piston anti-wear rings, automobile connecting rods, brake discs, engine pistons and gear boxes.

[0069] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0070] Example 1

[0071] Samples were loaded in a glove box filled with argon, and 99.5 vol.% fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% TiC nanoparticle reinforcement with a particle size = 50 nm were loaded into a tungsten steel can. The diameters of the steel balls were 8 mm, 6 mm, and 2 mm, respectively, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten steel can was sealed after being filled with argon and placed in a planetary ball mill. The speed of the planetary ball mill was 200 rpm, and it worked for 15 minutes and stopped for 10 minutes, for a total of 2 hours. The obtained mixed powder was used as the hard domain. And the coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm <150 μm was used as the soft domain.

[0072] Starting from the soft domain, the soft domain and the hard domain are stacked into nine layers in an alternating order, compacted and placed in a spark plasma sintering system, and heated and pressurized to obtain a cylindrical sample with a diameter of 45 mm and a height of 18 mm, and cooled with the furnace to obtain the sintered particle reinforced aluminum-based composite material of the present invention. The heating and pressurizing process is: 0min-2min temperature rises to 20°C; 2min-6min temperature rises to 100°C; 6min-12min temperature rises to 200°C; 12min-20min temperature rises to 300°C; 20min-32min rises to 400°C; 32min-48min temperature rises to 530°C; 48min-50min temperature rises to 540°C; 50min-52min rises to 550°C; 52min-54min temperature rises to 560°C; 54min-57min temperature remains at 560°C. The pressure remains at 50MPa from 2min to 57min.

[0073] Figure 2 This is the OM image of the sintered double heterogeneous particle reinforced aluminum-based composite material prepared in Example 1 of the present invention, wherein the average grain size of the coarse-grained region is 53 μm, the average grain size of the fine-grained region is 417 nm, and the boundaries are tightly bonded.

[0074] Example 2

[0075] Samples were loaded in a glove box filled with argon, and 99.5 vol.% of fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% of TiC nanoparticle reinforcement with a particle size = 50 nm were loaded into a tungsten steel can. The diameters of the steel balls were 8 mm, 6 mm, and 2 mm, respectively, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten steel can was sealed after being filled with argon and placed in a planetary ball mill. The speed of the planetary ball mill was 200 rpm, and it worked for 15 minutes and stopped for 10 minutes, for a total of 2 hours. The obtained mixed powder was used as the hard domain. And the coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm < <150 μm was used as the soft domain.

[0076] Starting from the soft domain, the soft domain and the hard domain are stacked into nine layers in an alternating order, compacted and placed in a spark plasma sintering system, and after heating and pressurization, a cylindrical sample with a diameter of 45 mm and a height of 18 mm is obtained, which is cooled with the furnace.

[0077] The cylindrical sample was subjected to multiple cold rolling passes, with a reduction of 10% each time and a total reduction of 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.

[0078] Figure 3 This is the OM image of the cold-rolled double heterogeneous particle reinforced aluminum-based composite material prepared in Example 2 of the present invention, wherein the gray area is the coarse-grained area, and the brown area is the fine-grained area. The grains in the coarse-grained area are elongated along the rolling direction, while the grains in the fine-grained area still maintain nanometer size.

[0079] Example 3

[0080] Samples were loaded in a glove box filled with argon, and 99.5 vol.% of fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% of TiC nanoparticle reinforcement with a particle size = 50 nm were loaded into a tungsten steel can. The diameters of the steel balls were 8 mm, 6 mm, and 2 mm, respectively, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten steel can was sealed after being filled with argon and placed in a planetary ball mill. The speed of the planetary ball mill was 200 rpm, and it worked for 15 minutes and stopped for 10 minutes, for a total of 2 hours. The obtained mixed powder was used as the hard domain. And the coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm < <150 μm was used as the soft domain.

[0081] Starting from the soft domain, the soft domain and the hard domain are stacked into nine layers in an alternating order, compacted and placed in a spark plasma sintering system, and heated and pressurized to obtain a cylindrical sample with a diameter of 45 mm and a height of 18 mm, which is then cooled with the furnace. The heating and pressurizing process is as follows: 0min-2min temperature rises to 20℃; 2min-6min temperature rises to 100℃; 6min-12min temperature rises to 200℃; 12min-20min temperature rises to 300℃; 20min-32min rises to 400℃; 32min-48min temperature rises to 530℃; 48min-50min temperature rises to 540℃; 50min-52min temperature rises to 550℃; 52min-54min temperature rises to 560℃; 54min-57min temperature remains at 560℃. The pressure remains at 50MPa from 2min to 57min.

[0082] The cylindrical sample was subjected to multiple cold rolling passes, with a reduction of 10% each time and a total reduction of 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.

[0083] The cold-rolled plate was placed in a muffle furnace, solution treated at 570°C for 5 min, and then water-cooled.

[0084] Figure 4 This is the OM diagram of the double heterogeneous particle reinforced aluminum-based composite material prepared in Example 3 of the present invention after 570°C solution heat treatment for 5 minutes, wherein the gray area is the coarse-grained area, the brown area is the fine-grained area, the grains in the coarse-grained area are elongated along the rolling direction, and the grains in the fine-grained area still maintain nanometer size.

[0085] Example 4

[0086] Samples were loaded in a glove box filled with argon, and 99.5 vol.% fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% TiC nanoparticle reinforcement with a particle size = 50 nm were loaded into a tungsten steel can. The diameters of the steel balls were 8 mm, 6 mm, and 2 mm, respectively, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten steel can was sealed after being filled with argon and placed in a planetary ball mill. The speed of the planetary ball mill was 200 rpm, and it worked for 15 minutes and stopped for 10 minutes, for a total of 2 hours. The obtained mixed powder was used as the hard domain. And the coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm <150 μm was used as the soft domain.

[0087] Starting from the soft domain, the soft domain and the hard domain are stacked into nine layers in an alternating order, compacted and placed in a spark plasma sintering system, and heated and pressurized to obtain a cylindrical sample with a diameter of 45 mm and a height of 18 mm, which is then cooled with the furnace. The heating and pressurizing process is as follows: 0min-2min temperature rises to 20℃; 2min-6min temperature rises to 100℃; 6min-12min temperature rises to 200℃; 12min-20min temperature rises to 300℃; 20min-32min rises to 400℃; 32min-48min temperature rises to 530℃; 48min-50min temperature rises to 540℃; 50min-52min temperature rises to 550℃; 52min-54min temperature rises to 560℃; 54min-57min temperature remains at 560℃. The pressure remains at 50MPa from 2min to 57min.

[0088] The cylindrical sample was subjected to multiple cold rolling passes, with a reduction of 10% each time and a total reduction of 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.

[0089] The cold-rolled plate was placed in a muffle furnace and solutionized at 570°C for 30 min, followed by water cooling.

[0090] Figure 5 This is the OM diagram of the double heterogeneous particle reinforced aluminum-based composite material prepared in Example 4 of the present invention after 570°C solution heat treatment for 30 minutes, wherein the gray area is the coarse-grained area, the brown area is the fine-grained area, the grains in the coarse-grained area are elongated along the rolling direction, and the grains in the fine-grained area still maintain nanometer size.

[0091] Example 5

[0092] Samples were loaded in a glove box filled with argon, and 99.5 vol.% fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% TiC nanoparticle reinforcement with a particle size = 50 nm were loaded into a tungsten steel can. The diameters of the steel balls were 8 mm, 6 mm, and 2 mm, respectively, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten steel can was sealed after being filled with argon and placed in a planetary ball mill. The speed of the planetary ball mill was 200 rpm, and it worked for 15 minutes and stopped for 10 minutes, for a total of 2 hours. The obtained mixed powder was used as the hard domain. And the coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm <150 μm was used as the soft domain.

[0093] Starting from the soft domain, the soft domain and the hard domain are stacked into nine layers in an alternating order, compacted and placed in a spark plasma sintering system, and after heating and pressurization, a cylindrical sample with a diameter of 45 mm and a height of 18 mm is obtained, which is cooled with the furnace.

[0094] The heating and pressurizing process is as follows: the temperature rises to 20°C from 0min to 2min; the temperature rises to 100°C from 2min to 6min; the temperature rises to 200°C from 6min to 12min; the temperature rises to 300°C from 12min to 20min; the temperature rises to 400°C from 20min to 32min; the temperature rises to 530°C from 32min to 48min; the temperature rises to 540°C from 48min to 50min; the temperature rises to 550°C from 50min to 52min; the temperature rises to 560°C from 52min to 54min; the temperature is kept at 560°C from 54min to 57min. The pressure is kept at 50MPa from 2min to 57min.

[0095] The cylindrical sample was subjected to multiple cold rolling passes, with a reduction of 10% each time and a total reduction of 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.

[0096] The cold-rolled sheet was placed in a muffle furnace and solutionized at 570°C for 60 min, followed by water cooling.

[0097] Figure 6 This is the OM diagram of the double heterogeneous particle reinforced aluminum-based composite material prepared in Example 5 of the present invention after 570°C solution heat treatment for 60 minutes, wherein the gray area is the coarse-grained area, the brown area is the fine-grained area, the grains in the coarse-grained area are elongated along the rolling direction, and some grains in the fine-grained area undergo secondary recrystallization.

[0098] Example 6

[0099] Samples were loaded in a glove box filled with argon, and 99.5 vol.% fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% TiC nanoparticle reinforcement with a particle size = 50 nm were loaded into a tungsten steel can. The diameters of the steel balls were 8 mm, 6 mm, and 2 mm, respectively, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten steel can was sealed after being filled with argon and placed in a planetary ball mill. The speed of the planetary ball mill was 200 rpm, and it worked for 15 minutes and stopped for 10 minutes, for a total of 2 hours. The obtained mixed powder was used as the hard domain. And the coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm <150 μm was used as the soft domain.

[0100] Starting from the soft domain, the soft domain and the hard domain are stacked into nine layers in an alternating order, compacted and placed in a spark plasma sintering system, and heated and pressurized to obtain a cylindrical sample with a diameter of 45 mm and a height of 18 mm, which is then cooled with the furnace. The heating and pressurizing process is as follows: 0min-2min temperature rises to 20℃; 2min-6min temperature rises to 100℃; 6min-12min temperature rises to 200℃; 12min-20min temperature rises to 300℃; 20min-32min rises to 400℃; 32min-48min temperature rises to 530℃; 48min-50min temperature rises to 540℃; 50min-52min temperature rises to 550℃; 52min-54min temperature rises to 560℃; 54min-57min temperature remains at 560℃. The pressure remains at 50MPa from 2min to 57min.

[0101] The cylindrical sample was subjected to multiple cold rolling passes, with a reduction of 10% each time and a total reduction of 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.

[0102] The cold-rolled plate was placed in a muffle furnace and solutionized at 570°C for 30 min, followed by water cooling.

[0103] The plate subjected to the solution heat treatment is placed in a muffle furnace, subjected to an aging heat treatment at 175° C. for 1 hour, and then air-cooled to obtain the high-strength and high-plasticity dual heterogeneous particle reinforced aluminum-based composite material of the present invention.

[0104] Figure 7 This is a TEM image of the double heterogeneous particle reinforced aluminum matrix composite material prepared in Example 6 of the present invention after aging heat treatment at 175°C for 1 hour. A large number of coherent GP regions and a small amount of coherent β" phase are distributed in the matrix, which is a typical under-failure state.

[0105] Example 7

[0106] Samples were loaded in a glove box filled with argon, and 99.5 vol.% fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% TiC nanoparticle reinforcement with a particle size = 50 nm were loaded into a tungsten steel can. The diameters of the steel balls were 8 mm, 6 mm, and 2 mm, respectively, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten steel can was sealed after being filled with argon and placed in a planetary ball mill. The speed of the planetary ball mill was 200 rpm, and it worked for 15 minutes and stopped for 10 minutes, for a total of 2 hours. The obtained mixed powder was used as the hard domain. And the coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm <150 μm was used as the soft domain.

[0107] Starting from the soft domain, the soft domain and the hard domain are stacked into nine layers in an alternating order, compacted and placed in a spark plasma sintering system, and after heating and pressurization, a cylindrical sample with a diameter of 45 mm and a height of 18 mm is obtained, which is cooled with the furnace.

[0108] The cylindrical sample was subjected to multiple cold rolling passes, with a reduction of 10% each time and a total reduction of 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.

[0109] The cold-rolled plate was placed in a muffle furnace and solutionized at 570°C for 30 min, followed by water cooling.

[0110] The plate subjected to the solution heat treatment is placed in a muffle furnace, subjected to an aging heat treatment at 175° C. for 3 hours, and then air-cooled to obtain the high-strength and high-plasticity dual heterogeneous particle reinforced aluminum-based composite material of the present invention.

[0111] Figure 8 This is a TEM image of the double heterogeneous particle reinforced aluminum matrix composite material after aging heat treatment at 175°C prepared in Example 7 of the present invention. A large amount of coherent β" phase is distributed in the matrix, which is the peak aging state and can ensure the high strength of the material.

[0112] Example 8

[0113] Samples were placed in a glove box filled with argon, and 99.5 vol.% fine-grained 6061 aluminum alloy (particle size <10 μm) and 0.5 vol.% TiC nanoparticle reinforcement (particle size = 50 nm) were placed in a tungsten steel can. The diameters of the steel balls were 8 mm, 6 mm, and 2 mm, respectively, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten steel can was sealed after being filled with argon and placed in a planetary ball mill. The speed of the planetary ball mill was 200 rpm, and it worked for 15 minutes and stopped for 10 minutes, for a total of 2 hours.

[0114] The powders were stacked into nine layers in an alternating order of coarse-grained 6061 aluminum alloy powder (45 μm < particle size < 150 μm) and fine-grained 6061 aluminum alloy powder (particle size < 10 μm) + TiC nanoparticle reinforcement (particle size = 50 nm), compacted and placed in a spark plasma sintering system. After heating and pressurization, cylindrical samples with a diameter of 45 mm and a height of 18 mm were obtained, which were then cooled in the furnace.

[0115] The cylindrical sample was subjected to multiple cold rolling passes, with a reduction of 10% each time and a total reduction of 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.

[0116] The cold-rolled plate was placed in a muffle furnace, solution treated at 570°C for 5 min, and then water-cooled.

[0117] The plate subjected to the solution heat treatment is placed in a muffle furnace, subjected to an aging heat treatment at a temperature of 175° C. for 5 hours, and then air-cooled to obtain the high-strength and high-plasticity dual heterogeneous particle reinforced aluminum-based composite material of the present invention.

[0118] Fig. 9 This is a TEM image of the double heterogeneous particle reinforced aluminum matrix composite material prepared in Example 8 of the present invention after aging heat treatment at 175° C. for 5 hours. A large amount of semi-coherent β' phase is distributed in the matrix, indicating an over-aging state.

[0119] Test Example 1

[0120] The products of Examples 2-8 were subjected to performance tests of yield strength, ultimate tensile strength and elongation, and the test standard was GB / T228-1987 "Metal Tensile Test Methods". The results are listed in Table 1. From the data in Table 1, it can be concluded that the yield strength of the double heterogeneous particle reinforced aluminum-based composite material prepared in Example 7 of the present invention is 379.4, the tensile strength is 405.7 MPa, and the total elongation is 12.7%, achieving high strength and high plasticity of the particle reinforced aluminum-based composite material.

[0121] Table 1 Mechanical property test results of the alloys prepared in Examples 2 to 8.

[0122]

[0123] As can be seen from the above table, the double heterogeneous particle reinforced aluminum-based composite material obtained in the preparation method of the double heterogeneous particle reinforced aluminum-based composite material proposed in the present invention has excellent mechanical properties with synergistic improvement of strength and plasticity. The results of the embodiments of the present invention show that the yield strength of the double heterogeneous particle reinforced aluminum-based composite material provided by the present invention is 379.4MPa, the ultimate tensile strength is 405.7MPa, and the elongation is 12.7%. Its comprehensive mechanical properties are significantly improved compared with the existing methods.

[0124] The embodiments described above are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A double heterogeneous particle reinforced aluminum matrix composite material, characterized in that: The invention comprises nine layers of soft domains and hard domains which are alternately stacked and cold-rolled. The soft domain is a homogeneous material of coarse-grained 6061 aluminum alloy, and the hard domain is a composite material composed of fine-grained 6061 aluminum alloy and TiC nanoparticle reinforcement.

2. The double heterogeneous particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The volume ratio of 6061 aluminum alloy to TiC nanoparticle reinforcement in the hard domain is 99.5:0.

5.

3. A method for preparing the double heterogeneous particle reinforced aluminum matrix composite material according to claim 1, characterized in that: It includes the following steps: S1, using the soft domain as the first layer and alternately stacking and compacting nine layers of hard domain and soft domain material powders to prepare a 9-layer composite material by spark plasma sintering; S2, performing multiple cold rolling on the composite material with a total reduction of 90%, and performing annealing at 400° C. for 10 min at a reduction of 50%; S3. After multiple cold rollings, the rolled composite material is heat treated, the heat treatment includes solution heat treatment and aging heat treatment, the insulation temperature of the solution heat treatment is 550-570°C, the insulation time of the solution heat treatment is 5-60min, the insulation temperature of the aging heat treatment is 150-200°C, the insulation time of the aging heat treatment is 1-5h, and after the heat treatment is completed, a double heterogeneous particle reinforced aluminum-based composite material is obtained.

4. The preparation method according to claim 3, characterized in that: In step S3, the solution heat treatment is performed at a holding temperature of 570° C. and a holding time of 30 min. In step S3, the aging heat treatment has a holding temperature of 175° C. and a holding time of 3 h.

5. The preparation method according to claim 3, characterized in that: The composite material after cold rolling includes three deformation stages. The first deformation stage is an elastic deformation process, which is the same as that of the homogeneous material; The second deformation stage is an elastic-plastic transition process. Stress activates the dislocation source in the soft domain to cause plastic deformation, while the hard domain still maintains elastic strain, resulting in mechanical incompatibility. The hard domain constraint restricts and increases the strain of the soft domain. A strain gradient is generated at the domain interface. The properties of the soft and hard domains are changed through the coordination of geometrically necessary dislocations, thereby improving the overall yield strength. Dislocations accumulate at the interface of the soft domain. The dislocation source needs to increase stress to stimulate dislocations. Heterogeneous deformation-induced stress is generated through the accumulation of geometrically necessary dislocations, thereby strengthening the soft domain. The third deformation stage is the surface strain distribution process. Continuous strain causes the hard domain to begin plastic deformation, and strain distribution increases the strain of the soft domain. The strain gradient at the boundary between the soft domain and the hard domain increases. The accumulation of a large number of geometrically necessary dislocations provides strain hardening ability to prevent necking, so that the composite material has both high strength and high plasticity.

6. The preparation method according to claim 3, characterized in that: Step S1 specifically includes the following sub-steps: S11, preparing hard domain powder: putting 99.5 vol.% 6061 aluminum alloy powder and 0.5 vol.% TiC nanoparticle reinforcement into a planetary ball mill for ball milling and mixing, wherein the planetary ball mill includes three kinds of steel balls, the diameters of the three kinds of steel balls are 8 mm, 6 mm, and 2 mm, respectively, the mass ratio is 2:3:5, and the ball-to-material ratio is 8:1, to obtain the hard domain powder after ball milling; S12. Alternately stack 9 layers of coarse-grained 6061 aluminum alloy powder and ball-milled hard domain powder, compact them, and place them in a spark plasma sintering system to apply temperature and pressure to prepare a sintered 9-layer composite material.

7. The preparation method according to claim 3, characterized in that: The obtained double heterogeneous particle reinforced aluminum matrix composite material has a yield strength of 379.4 MPa, an ultimate tensile strength of 405.7 MPa, and an elongation of 12.7%.

8. The preparation method according to claim 3, characterized in that: The particle size of fine-grained 6061 aluminum alloy powder is <10 microns, the particle size of TiC nanoparticle reinforcement is 50 nanometers, and the particle size of coarse-grained 6061 aluminum alloy powder is greater than 45 microns and less than 150 microns.

9. The preparation method according to claim 3, characterized in that: In step S11, argon is used as the protective atmosphere during the powder loading process; the planetary ball mill works for a total time of 2-2.5 hours, and stops for 10 minutes after working for 15 minutes, with a rotation speed of 150-200 rpm.

10. The preparation method according to claim 3, characterized in that: In step S12, the sintering temperature and pressure increase process is: the temperature is increased to 20°C from 0min to 2min; the temperature is increased to 100°C from 2min to 6min; the temperature is increased to 200°C from 6min to 12min; the temperature is increased to 300°C from 12min to 20min; the temperature is increased to 400°C from 20min to 32min; the temperature is increased to 530°C from 32min to 48min; the temperature is increased to 540°C from 48min to 50min; the temperature is increased to 550°C from 50min to 52min; the temperature is increased to 560°C from 52min to 54min; the temperature is maintained at 560°C from 54min to 57min; and the pressure is maintained at 50MPa from 2min to 57min.

Citation Information

Patent Citations

  • Preparation method for composite panel of aluminum alloy / aluminum-based composite material

    CN110480018A

  • Aluminum alloy profile with mixed crystal heterostructure characteristic and preparation method

    CN116479281A

  • Method for developing superplasticity of titanium carbide reinforced aluminum alloy composite material

    JP1994235032A

  • Manufacturing method for aluminium alloy billet

    JP2017094391A

  • Method of producing uniform blends of NANO and micron powders

    WO2008034043A2